Infrageneric reclassification and phylogenetic inference in the genus Masdevallia Ruiz & Pav. (Orchidaceae, Pleurothallidinae) n preliminary results of nrDNA based analysis - Matuszkiewicz, Aleksandra; Tukałło, Piotr (Biodiversity: Research and Conservation, 2006)
The genus Masdevallia is one of the largest genera within the subtribe Pleurothallidinae. Its present infrageneric classification, based on easily recognized morphological features, does not reflect natural relationships and evolutionary trends within the genus. To test its relative utility in infrageneric classification and in resolving genus phylogeny, sequences of the Internal Transcribed Spacer region (ITS1-5,8S-ITS2) were identified for 37 taxa and combined with additional 35 sequences taken from the GenBank. Results of maximum parsimony based on phylogenetic analysis indicate that the level of sequence divergence is sufficient to resolve infrageneric relationships. The implications of current results for the classification of Masdevallia are also briefly discussed. Many of the infrageneric changes made by C.A. Luer since his first classification of the genus in 1986 are not supported by results of this study.